Evaluation of Pregnancy Outcome in Women with Rheumatic Mitral Valve Stenosis - Koirala, Poonam; Ghimire, Asmita; Ojha, Neebha; Koirala, Ishita (Nepalese Heart Journal, 2023)
Background and Aims: Rheumatic heart disease is still one of the most common heart lesion in developing countries. The maternal and fetal hazards increase with the severity of Mitral stenosis. This study was aimed to determine the fetomaternal outcome in women with mitral stenosis during pregnancy. Methods: This was descriptive cross-sectional study which included all pregnant patients with isolated rheumatic mitral valve stenosis. Major adverse outcomes studied were cardiac failure, thromboembolic event, admission in cardiac care or intensive care unit, atrial fibrillation, endocarditis, pulmonary hypertension and cardiac death. Results: Out of 3194 pregnant women, 31 had mitral stenosis. Their mean age was 27 years, mean mitral valve area 1.43cm2 and majority were primigravida (61.29%). Among them, symptomatic cardiac failure was present in 6.66%, 30% and 66.66% of mild, moderate and severe mitral stenosis respectively. The chances of cardiac failure, atrial fibrillation, preterm delivery and small for gestational age babies was high in all patients without having percutaneous trans-luminal mitral commissurotomy than those who underwent the procedure for moderate to severe mitral stenosis during pregnancy. Conclusion: There were high chances of adverse fetomaternal outcome in pregnant women with mitral stenosis. Cardiac failure was found to be increased with the severity of mitral stenosis. PTMC during pregnancy resulted in decreased cardiac failure, atrial fibrillation, preterm delivery and small for gestational age babies.